EXEMPLARY MODEL OF GOOGLE TRANSLATE UTILIZATION IN ENHANCING ARABIC LANGUAGE ACQUISITION AMONG MALAY LEARNERS - Dr. Muhamadul Bakir Hj. Yaakub (Journal of Islamic, Social, Economics and Development, 2021)
This article focuses on introducing an exemplary model for Malay learners of Arabic language in using Google Translate to fulfil their language needs and necessities which is regarded as a natural social reaction within multi-racial societies, especially in the occasion of problem-solving and self-regulated learning strategies. This exploratory study was prompted by the question â€œDoes using Google translate fulfil my language needs?â€ when used according to its guidelines, students improve their language acquisition and capability to translate texts with fewer syntactic and semantic errors. The model was develop based on Leonardiâ€™s (2011) call for a re-evaluation and a rehabilitation of the translation activities in their foreign language classes. The findings also show that there are various forms of translation mistakes and difficulties confronted by Malay learners of Arabic language. Itâ€™s caused by ineffective usage of the software for the purpose of second language acquisition. This study proposes an exemplary model of application procedures and analysis of machine translation output based on identification of its semantics and pragmatics aspects. For this study, the proposed model was tested with small sampling in an unofficial classroom and is yet to be tested within a comprehensive official classroom in the future research. As per the main objective, which is addressing student awareness of Google Translate shortcomings and disadvantages. Therein, they will become more responsible and critical in nature to search for supports and solutions. Consequently, more empirical data will be needed for this achievement. Obviously, the issue of this study is very much timely, especially in term of teacher-student engagement in analyzing linguistics features of language usage.